Topology and control strategy optimization of an auxiliary resonant commutated pole-based, soft-switching grid-connected inverter - Liu, Chuang; Wang, Yanping (Frontiers in Energy Research, 2023)
With the development of new energy industries such as photovoltaics. Microgrids or distributed energy sources require a lot of DC-AC grid-connected interfaces. How to reduce the switching loss of inverter is important to improve the transmission efficiency of inverter, reduce the heat generation of inverter, promote the high frequency and miniaturization of inverter, as well as for the efficient use of distributed energy. Therefore, considering the wide application of DC-AC power electronic interface in microgrid and distributed energy, and in order to make up for the deficiencies existing in traditional hard-switching inverters. In this paper, an optimal control strategy and topology for an auxiliary resonant commutated pole inverter (O-ARCP) is proposed. The topology proposed in this paper can divide the control mode of the auxiliary circuit into two time periods according to the direction of the load current. When the load current direction is different and the working auxiliary circuits are different, the additional loss caused by two sets of auxiliary circuits working at the same time can be avoided. At the same time, the control method of the auxiliary circuit is simplified, making control easy. At the same time, diodes are connected in series in the auxiliary working circuit to reduce the losses generated by the resonant inductor current return. After simulation and experiment testing, it is proved that all switches of the proposed topology are in soft switching mode, which proves the effectiveness of the proposed control strategy and analysis.